Flavonoids and triterpenoids from Callistemon citrinus and their inhibitory effect on no production in LPS-stimulated RAW264.7 macrophages - Cuong, Nguyen Manh; Khanh, Pham Ngoc; Duc, Ho Viet; Huong, Tran Thu; Kim, Youn-Chui; Long, Pham Quoc; Kim, Young Ho (Vietnam Journal of Science and Technology, 2016)
Phytochemical investigation of the leaves and stems of Callistemon citrinus (Curtis) Skeels led to the isolation of 12 flavonoid and triterpenoid compounds, including one new flavonoid, callistine A (1) and six known flavonoids 6,7- dimethyl-5,7-dihydroxy-4’-methoxy flavone (2), astragalin (3), quercetin (4), catechin (5), eucalyptin (6), and 8-demethyleucalyptin (7), along with 5 triterpenoids, 3-β-acetylmorolic acid (8), 3β-hydroxy-urs-11-en-13(28)-olide (9), betulinic acid (10), diospyrolide (11) and ursolic acid (12). Their chemical structures were determined from the spectroscopic evidences counting 1D- and 2D-NMR and HR-MS data. All the isolated compounds were examined for their anti-inflammatory activity against LPS-activated NO production in macrophage RAW264.7 cells. Among them, quercetin (4) and 3β-hydroxy-urs-11-en-13(28)-olide (9) showed potential inhibition activity in nitric oxide (NO) production in RAW264.7 cells exposed to LPS.